2019
DOI: 10.1002/jmri.26832
|View full text |Cite
|
Sign up to set email alerts
|

Aortic dilatation associates with flow displacement and increased circumferential wall shear stress in patients without aortic stenosis: A prospective clinical study

Abstract: BackgroundThe relationship between blood flow characteristics and ascending aortic (AA) dilatation has not been studied in patients with a tricuspid aortic valve (TAV) without aortic stenosis. PurposeTo evaluate whether four-dimensional (4D) flow characteristics determined in MRI are related to AA dilatation by comparing dilated AA and non-dilated AA subjects with TAV. Study type Prospective.Population 20 patients with dilated AA, 20 age-matched patients with non-dilated AA. Field Strength/Sequence1.5T/4D flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Intra-and interobserver reproducibility analyses for measurements of AA diameter were not performed in the present study. However, in our prior study with 1.5-T aortic magnetic resonance angiography, interobserver reproducibility was shown to be excellent (ICC = 0.917) with 20 dilated AA and 20 non-dilated AA patients [7]. Lu et al showed in a small 30-patient CT population that the maximum variability was 1.2 mm in the measured AA diameter and low variability indicated that AA diameter is a reliable measurement [25].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Intra-and interobserver reproducibility analyses for measurements of AA diameter were not performed in the present study. However, in our prior study with 1.5-T aortic magnetic resonance angiography, interobserver reproducibility was shown to be excellent (ICC = 0.917) with 20 dilated AA and 20 non-dilated AA patients [7]. Lu et al showed in a small 30-patient CT population that the maximum variability was 1.2 mm in the measured AA diameter and low variability indicated that AA diameter is a reliable measurement [25].…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, it has been related to hypertension and smoking [4][5][6]. The hemodynamic conditions in the aorta play a significant role in determining TAD [7]. In particular, the bicuspid aortic valve (BAV) often causes valvular dysfunction (stenosis and regurgitation) and abnormal flow in the ascending aorta.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that somehow bigger and longer helices with a "mismatch" between the volume of the helix and aorta could lead to aortic dilatation or elevated wall shear stress 21,31,32 . However, further studies are needed to evaluate which parameters are best for the assessment of pathologic flow patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Increased WSS has been associated with aortic dilatation 32 , 33 , endothelial cell dysfunction 34 , 35 , development of atherosclerotic plaque 36 , as well as the formation of intracranial aneurysms 31 . WSS and secondary flow have already shown to be increased in patients with aortic coarctation 37 , 38 at rest.…”
Section: Discussionmentioning
confidence: 99%